Frank F. Brightley, A Digest of the Laws and Ordinances of the City of Philadelphia 513 (1887) - (:unkn) unknown (My University, 1887)
Commissioners of Fairmount Park, art. VII, § 57, pt. 2: Prohibited carry of firearms, shooting of birds, or throwing stones or missiles within fifty yards of Fairmount Park.
Keywords: CARRY - CERTAIN PUBLIC PLACES; DISCHARGE